Penerapan Metode TOPSIS untuk Pemeringkatan Saham Jakarta Islamic Index 70 - Zulfiandri Zulfiandri; Balqis Aulia Rahma; Zafira Fayyaza Lutfun Nisa; Farah Adila; Rinda Hesti Kusumaningtyas (Bulletin of Computer Science Research, 2025)
This study aims to evaluate and rank sharia stocks included in the Jakarta Islamic Index 70 (JII70) as a basis for investment recommendations based on fundamental performance. The problem discussed is the need for investors to have an objective and structured decision-making model in selecting sharia stocks, considering the large number of stock alternatives available in the JII70 index. This study uses the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method implemented using RStudio. Of the total 70 stocks in the JII70 index, this study analyzes five sharia issuers, namely TLKM, CTRA, ADRO, KLBF, and ICBP, which were selected purposively based on their level of liquidity, availability of financial ratio data, and cross-sector representation of the industry. The criteria used include Price to Earnings Ratio (PER), Price to Book Value (PBV), Return on Equity (ROE), Debt to Equity Ratio (DER), and Net Profit Margin (NPM). The criteria weighting was conducted using a subjective approach based on investor preferences, considering the relative importance of each ratio to investment decisions. The results of the study show that PT Adaro Energy Indonesia Tbk (ADRO) consistently obtained the highest preference value with a value of 0.771, followed by PT Ciputra Development Tbk (CTRA) in second place. These findings demonstrate that the TOPSIS method is capable of providing a systematic and transparent ranking of sharia stocks, although this study has limitations in the number of issuer samples analyzed. Future research can expand the number of issuers and add macroeconomic criteria.